Pendekatan Humor dalam REBT terhadap Kecemasan Akibat Fear of Missing Out (FOMO): Studi Literatur - Siti Nur Halizah; Chalisah Salsabila Widodo; Jumi’ati Afifah; Daffa Anugrah Putra; Muhamad Afifuddin Ghozali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This literature review aims to examine the effectiveness of a humorous approach in Rational Emotive Behavior Therapy (REBT) in addressing anxiety caused by Fear of Missing Out (FOMO). The background to this research is the increasing prevalence of FOMO as a form of modern social anxiety triggered by social media use. The research method used was a systematic integrative review, combining the results of quantitative, qualitative, and theoretical research articles. The results indicate that humor in REBT is effective in reducing FOMO anxiety by addressing irrational beliefs, decreasing emotional reactivity, and facilitating cognitive transformation. Humor helps individuals view social situations from a more adaptive perspective, increases self-acceptance, and reduces compulsive behaviors related to social media. This study concludes that integrating humor into REBT can be an effective strategy for addressing FOMO anxiety among students.